Influence of semicircular canal morphology on the VOR and swimming activity in larval amphibians: a comparative study in Xenopus and axolotl - Parthena Schneider-Soupiadis; Parthena Schneider-Soupiadis; Michael Forsthofer; Michael Forsthofer; Michael Forsthofer; Felix Schneider-Soupiadis; Felix Schneider-Soupiadis; Gilles Courtand; Rosario Sanchez-Gonzalez; François M. Lambert; Hans Straka (Frontiers in Neurology)
Gaze stabilization and locomotion rely often on an accurate sensory detection of head movements by the vestibular system. A functional relationship between vestibular sensitivity, locomotor skills and semicircular canal morphology has been suspected in vertebrates as an adaptation to eco-physiological and species-specific needs, but has only partially and indirectly documented. However, evaluating the vestibulo-ocular reflexive activity and the locomotor efficiency simultaneously with the rotational sensor geometry remains absent from the literature. From such a perspective, this study attempted to provide a simultaneous quantification of the vestibulo-ocular response, the swimming efficiency and the canal morphology in the salamander axolotl and the frog Xenopus laevis, two amphibian species with comparable lifestyle and identical locomotor and vestibular systems at larval stages. Animals were studied at an equivalent developmental period: the late pre-metamorphic stage where the hindlimbs start to differentiate. Larval axolotl demonstrated an angular vestibulo-ocular reflex (aVOR) with a gain ~83% lower than Xenopus. Like in Xenopus at earlier stages, the aVOR gain increased in axolotl indicating a later functional onset. The morphological comparison of the semicircular canals of both species revealed that the horizontal canal in axolotl was thinner, less curved and less coplanar to the horizontal plane compared to Xenopus. Additionally, the ampulla of Xenopus was rounder and less elongated than in axolotl. All these parameters are critical for endolymph flow and consequently for the capacity of semicircular canals to perceive head motion. Interestingly, axolotl demonstrated a reduced swimming activity, more episodic than Xenopus, resulting in less frequent exposure to important head accelerations. Altogether, our results provide correlative evidences for a clear functional link between semicircular canal morphology, vestibular sensitivity, influencing aVOR performance, but also locomotor capacity in two comparable species, representative of anuran and salamander amphibians. This study, even preliminary, should open the pathway for further and more complete demonstrations of this functional relationship, that seems to be commonly shared during the evolution.